Effect of increasing doses of nitrogen and sulphur on chemical composition of plants, yields and seed quality in winter rape - L. Hřivna; R. Richter; T. Lošák; J. Hlušek (Plant, Soil and Environment, 2002)
In 1999, the effect of increasing levels of nitrogen at the initial (13.9 mg.kg-1) and increased (40 mg.kg-1) level of watersoluble sulphur (Swat) was studied in winter rape (cv. Lirajet) grown in pots. A synergetic effect of nitrogen on concentrations of Ca and Mg was demonstrated in the growth stages DC 20-29 and 31-39. Levels of P and K were balanced. In variants with a low content of Swat in soil to 40 mg.kg-1 of soil S concentration increased. With the increasing dose of N the content of S decreased from 1.00% to 0.78% and from 0.68% to 0.38% in DC 20-29 and DC 31-39, respectively. An increased level of S in soil changed the ratio N/S. In variants with a natural (i.e. low) content of S in soil, this ratio widened with the increasing dose of N from 8.06 to 25.15 while in variants with an increased level of S in soil it ranged from 3.24 to 5.85 in the growth stage DC 20-29. Increasing doses of N widened the ratio N/P regardless to concentration of S in plants. In individual growth stages the ratio P/S was markedly narrowed by changing contents of S in soil. The highest yields were obtained in the variant with an optimum concentration of all elements in plants and S contents above 0.6% and/or about 0.4% in growth stages DC 20-29 and DC 31-39, respectively. The obtained yields demonstrated a highly significant effect of N and S on seed yields. At a low concentration of sulphur in plants the yield of seed increased only to the dose N3(i.e. 0.9 g N per pot); thereafter, it gradually decreased. An increased level of S in soil showed a positive effect on seed yields. Higher doses of N widened the ratio straw/seeds from 2.46 to 7.69; at higher levels of S in soil, an opposite trend was observed. In variants with a low content of S the number of branches and pods increased proportionally with increasing doses of N. On the other hand, increased levels of S reduced the number of branches and pods. At a low level of S in soil the total weight of seeds per pod decreased with the increased supply of N from 69.9 mg to 20.4 mg. At increased levels of S the weight of seeds per pod increased from 61.9 mg to 79.8 mg. Results of field experiments in four different localities corroborated a positive effect of S (in interaction with N) on its concentration in plants. The seed yield was significantly increased. In 2000, results from all localities were markedly influenced by climatic conditions; however average results of all experiments showed that S increased seed yields depending on the dose of N by 2.5 and 5.9%. An optimum nutrition of plants with all elements (including S) results in improved utilisation and increased yields.